KESANTUNAN BERBAHASA MELALUI UNGKAPAN BASA- BASI DALAM BAHASA JEPANG - Ni Made Andry Anita Dewi (Journal Social and Humaniora, 2017)
Politeness speech through the courtesy expression is a basis for developing e?ective. In Japanese society, courtesy expression is used both in the family environment and the workplace. With this phenomen, this paper is focused on politeness speech through the courtesy expression in Japanese. Politeness speech through the courtesy expression can be classifying into six maxims. These maxims are maxim of wisdom, generosity maxims, award, simplicity maxims, maxims comunication in a community. Courtesy expression in Japanese is a speech that used to grow and develop conversation that take place between two or more speakers to strengthen their relationship of agreement and sympathy. Classification of sixth maxim by Leech does fulfill politeness speech through the courtesy expression. courtesy expression Keywords: politeness, politeness speech,